2020
DOI: 10.1155/2020/3681382
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Research and Characterization of the Loess Microstructure in the Bai Lu Tableland, Shaanxi Province, China

Abstract: Loess is a special geotechnical material with strong structural properties, and the microstructural characteristics of loess significantly influence its macroscopic physical features, mechanical properties, and catastrophic behavior. In this paper, serial samples were extracted from the continuous loess and paleosol strata of the Bai Lu tableland; with these samples, the optical microscopy-based serial sectioning method was adopted to study the quantitative characterization and variation in the loess microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Moreover, previous studies showed that there were intra-aggregate pores between the silt/clay particles within the aggregates [8]. The aggregates and bi-modal pore size distribution were widely observed in previous studies on compacted silty and clayey soils [8,10,29,30]. At the optimum water content and wet side of optimum water content, the images also show aggregates and bi-modal pore size distributions.…”
Section: Results Interpretationsmentioning
confidence: 56%
“…Moreover, previous studies showed that there were intra-aggregate pores between the silt/clay particles within the aggregates [8]. The aggregates and bi-modal pore size distribution were widely observed in previous studies on compacted silty and clayey soils [8,10,29,30]. At the optimum water content and wet side of optimum water content, the images also show aggregates and bi-modal pore size distributions.…”
Section: Results Interpretationsmentioning
confidence: 56%
“…As it was di cult to de ne the volume of pore connectivity, frequency percentages for the pore connectivity parameters were counted by number (Figs. [7][8][9][10][11], while those for the other parameters were counted by volume (Fig. 12).…”
Section: Representative Elementary Volumementioning
confidence: 99%
“…Microscopy-based observation methods, such as scanning electron microscopy and optical microscope, can provide visual information of the soil microstructure from natural or epoxy resin sections and are thus the most common tool for two-dimensional (2D) microstructure research. Numerous studies have adopted these methods to qualitatively investigate the microstructure of loess, including its particle, pore, and contact characteristics, and an increasing number of studies have quantitatively analyzed the loess microstructure in terms of size, shape, and arrangement, by combining these methods with image processing techniques (Deng et al 2020;Giménez et al 2012;Assallay 1998;Gao 1988). Recently researchers began to analyze the three-dimensional (3D) loess microstructure with the development of X-ray CT that can provide nondestructive testing (Li and Shao 2020; Yu et al 2020;Wei et al 2020;Li et al 2019;Wei et al 2019;Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of observation techniques and image processing technology, such as the application of optical microscope, scanning electron microscope (SEM), mercury intrusion method, nuclear magnetic resonance (NMR), and computed tomography (CT), scholars have conducted more specific and detailed research on the microstructure characteristics of loess including particle morphology, pore distribution, particle contact, connection, and arrangement, and have achieved remarkable results [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%